Trauma-Focused Cognitive Behavioral Therapy to reduce symptoms of post-traumatic stress disorder in adolescent victims of incest - Rakhmasari, Vriska Putri; Nashori, Fuad; Kurniawan, Yudi (Psikohumaniora: Jurnal Penelitian Psikologi, 2021)
The threat of sexual violence can occur anywhere, including in the family environment. The subject of this study was a fifteen-year-old girl with a diagnosis of post-traumatic stress disorder who had been a victim of incest by her stepfather. The study aims to examine the effectiveness of trauma-focused cognitive behavioral therapy to reduce symptoms of post-traumatic stress disorder. It uses a Single Case-Single Subject ABA design. The intervention involved 12 sessions of trauma-focused cognitive-behavioral therapy. Symptoms of posttraumatic stress disorder were measured by the Child Posttraumatic Stress Disorder Symptom Scale (CPSS). There was a change in the CPSS scores in the intervention and post-intervention processes, with the post-traumatic stress disorder scores changing from the moderate to the mild category of post-traumatic stress disorder. The decrease in the scores was also evidenced by the results of the different pre-intervention, intervention, and post-intervention CPSS scores using Mann-Whitney nonparametric analysis. The study has implications for the application of trauma-focused cognitive-behavioral therapy to reduce symptoms of post-traumatic stress disorder in adolescent girls who are victims of incest.